Stress intensity factors of cracked tubular t/y-joints under out-of-plane bending - Yee, Chang Wah (2014)
This report will focus mainly on the determination of the stress intensity factors of cracked tubular T/Y-joints containing a surface crack at the hot spot stress location. The cracked tubular T/Y-joints are subjected to out-of-plan bending load. A systematic mesh generator allows cracked tubular T/Y-joints to be formed and analyzed through Finite Element (FE) analysis. Stress intensity factor obtained from FE analysis taking advantage of the FE models generated by the new mesh generator is determined. After then, it is compared against results from the proposed equation existing in BS7910, to verify the accuracy of the proposed equation. A total of 72 models are studied in this report with varying parameters such as β, γ, τ, θ, a/t0 and c/a. The change occurring due to the various parameters will be observed and noticeable changes to the final results due to such changes will be listed down in the report.